2011
DOI: 10.1055/s-0031-1275742
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Endurance in Elite Football Players

Abstract: We aimed to improve the physical capacity of a top-level elite football team during its pre-season by implementing a maximal strength and high-intensity endurance training program. 21 first league elite football players (20-31 yrs, height 171-194 cm, mass 58.8-88.1 kg) having recently participated in the UEFA Champions' League, took part in the study. Aerobic interval-training at 90-95% of maximal heart rate and half-squats strength training with maximum loads in 4 repetitions × 4 sets were performed concurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
119
1
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(161 citation statements)
references
References 28 publications
(60 reference statements)
12
119
1
11
Order By: Relevance
“…Moreover, these results suggested that the order of completion of the program, E + RE or RE + E, did not influence the performance adaptations. These results [38] and others [2,37] may support, at least in part, the better compatibility between high-intensity modes of strength and endurance training.…”
Section: Soccer: a Concurrent Modalitysupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, these results suggested that the order of completion of the program, E + RE or RE + E, did not influence the performance adaptations. These results [38] and others [2,37] may support, at least in part, the better compatibility between high-intensity modes of strength and endurance training.…”
Section: Soccer: a Concurrent Modalitysupporting
confidence: 66%
“…The speed of movement ranged from 0.8 to 1.2 m.s −1 . ST complemented with sprint exercises with loads (5 kg) including change of direction movements, and 15- to 20-m take-offs with resisted sled-towing (10 kg)2×/wk/16 wksPS-IS↑ 6.8% CMJ (20 kg) ↑ 5.8% Fsquats 20kg ↑ 7.1% Fsquats 30kg ↑ 5.2% Fsquats 40kg ↓ 2.3% T 20m ↓ 2.4% T 30m ↓ 3.2% T st/10-20-m ↓ 1.6% T st/10-30-m ↓ 2.6% T st/20-30-m Helgerud et al, [37]Elite/Spain/23 (25; range 20 to 31)ET: 4 × 4 min at a treadmill (5.5% inclination) 90% to 95% HRmax separated by 3-min jogging at 50% to 60% HRmax ST: 4 sets × 4RM half-squats 90° with 3-min rest between sets2×/wk/8 wksPS↑ 8.6% VO 2 max ↑ 3.7% RE (11km.h) ↑ 52% 1RM HS ↑ 49% 1RM/BW↑ 3.2% T 10m ↑ 1.6% T 20m ↑ 5.2% CMJJovanovic et al [24]Elite junior/Croatia/50 (19)RST: 2 session a wk targeting the major muscle groups (e.g., legs, back, and chets) with workouts focusing power development (e.g., jump squat, squats, and bench throws) with loads up to 75% to 85% 1RM; SAQ: 3 sessions a wk, work:rest ratio of 3:2; ET: 1 session a wk, 4 × 4 min at 90% to 95% HRmax, 3 min rec 55% to 65% HRmax)8 wks (1st 8 wks in-season)IS↑ 2.1% T 5m ↑ 3.7% T 10m ↑ 1% CMJ ↑ 0.8% CJS ↔ SJ, maximal CMJMcGawley and Andersson [38]Semi-professional and professional players/Sweden/9 (23 ± 4)ET + ST Tuesday: RSA + speed endurance (e.g., 2× [7× (30 s on/90 s off)] ~95%, 3-min rest: reps 3 and 6 with ball) + 2nd session: RST (e.g., 3 × 5 cleans, 2 × 10 squats, 3 × 10 nordic hamstrings, 2 × 10 core rotations, 3 × 10 barbell rowing; 75%. 60- to 90-s rest); Thursday: (e.g., 2× [8× 45 s on/12 s off) agility/SAQ circuit] ~95% + 1 session functional strength (e.g., 2 × 8 lunges, 2 × 10 hamstrings kicks, 2 × 8 sideway lunges, 2 × 10 standing chest press, 2 × 10 crunches: 75%, 60 to 90s rest); Friday: (e.g., dribble track 4 × 4 min/3 min active rest; 90% to 95%, alternate ball) + 1 session PT (e.g., 3 × 4 Borzov jumps/3 × 10 core rotations; 3 × 6 bounding jumps/3 × 20 ball bounces; 3 × 15 toe bounding/3 × 20 fast shifting lunges)3×/wk/5 wksPS↑ 7.6% fat (%) ↑ 6% fat (kg) ↑ 1.5% lean mass (%) ↑ 3% lean mass (kg) ↑ 18.7% 1RM half-squat ↑ 28.5% 1RM lunge ↑ 97.3% iliopsoas (°) ↑ 5.3% hamstrings (°)↑ 1.4% T 10m ↑ 7% CMJ ↑ 1.1% agility ↑ 1.9% RSA ↑ 19.6% perf dec RSA ↑ 15.4% YYIR2 ↑ 65.3% chins ↑ 14.5% hanging sit-upsSemi-professional and professional players/ Sweden/ 9 (23 ± 4)ST + ET the same daily training but the inverse order (1st, the strength training and after endurance training)3×/wk/7 wksPS↑ 7.1% fat (%) ↑ 5.2% fat (kg) ↑ 1.6% lean (%) ↑ 3.6% lean (kg) ↑ 19.1% 1RM half-squat ↑ 19.1% 1RM lunge ↑ 165.2% iliopsoas (°) ↑ 10.3% hamstrings (°)↑ 2.2% T 10m ↑ 1.9% CMJ ↑ 0.9% agility ↑ 0.8% RSA ↑ 16.8% perf dec RSA ↑ 22.9% YYIR2 ↑ 22.9% chins ↑ 9.7% hanging sit-ups

↑, significant improvement; ↓, significant decrement; ↔, no significant alterations; ~ , approximately; NS , not specified; F/D , frequency and duration of training protocols; P , period of the soccer season; ST, strength training; ET, endurance training; SJ, squat jump; CMJ, countermovement jump; CMJWAS, countermovement jump with arm swing; MAS, maximal aerobic speed; VJ, vertical jump; Fsquats (20...

…”
Section: General Physiological Considerations Of Strength/power Trainingmentioning
confidence: 99%
“…Compared with undertaking RE alone, concurrent training attenuates skeletal muscle hypertrophy and maximal strength development in some (10,19,33,48,53), but not all (5,58,63,75,76), studies. Given that skeletal muscle mass plays an important role in overall metabolic health (87), and many athletes require elements of strength and muscle hypertrophy, concomitantly with a high aerobic capacity (47), minimizing interference during concurrent training has implications for optimizing both health and performance outcomes.…”
mentioning
confidence: 99%
“…In this regard, it has been reported that jump height, 10-m sprint, and 30-m sprint performances are correlated (r = 0.78, 0.94, and 0.71, respectively) with maximal muscular strength in professional soccer players (39). The positive effects of resistance training (RT) on strength, jumping, and sprinting abilities in adult soccer players have been widely studied (17,18). Nevertheless, the effect of RT on endurance in soccer players has received less scientific attention.…”
mentioning
confidence: 99%